Reclaiming Meaning in the Age of Intelligent Machines: Spiritual Intelligence and Human-Centered AI in English Language Teaching - Hossein Isaee; Hamehnaz Gholipour; Hamed Barjesteh; Shaghayegh Shirzad (Indonesian Journal of Pedagogy and Teacher Education, 2026)
Background: The rapid expansion of artificial intelligence (AI) in English language teaching (ELT) has increased opportunities for personalized learning, automated feedback, and instructional efficiency. However, growing reliance on AI raises concerns regarding meaning-making, ethical-responsibility, human-agency, and the preservation of educational purpose. Although research on AI-mediated ELT and spiritual intelligence (SI) has expanded, the relationship between these domains remains underexplored. Aims: This conceptual paper aims to 1) examine major theories of SI and their educational relevance, 2) analyze the ethical and human limitations of AI in ELT, and 3) propose a human-centered framework for spiritually intelligent AI-mediated language teaching. Methods: The study adopts a conceptual–integrative methodology drawing on interdisciplinary scholarship from SI, AI ethics, psychology, educational technology, and language education. Relevant literature was analyzed through concept extraction, thematic synthesis, and cross-disciplinary comparison to identify convergent themes and theoretical tensions. Results: The synthesis suggests that SI provides a valuable lens for understanding meaning-making, ethical sensitivity, self-awareness, reflective judgment, and learner agency in AI-supported learning environments. It indicates that while AI can simulate communication, it operates without subjective consciousness, lived experience, or autonomous moral accountability. The paper proposes a conceptual framework in which SI mediates the integration of AI into ELT through reflective pedagogy, ethical communication, teacher agency, and learner sense-making. Conclusion: The proposed framework highlights the importance of preserving human-centered values in AI-mediated language education. By connecting SI with AI-supported ELT, the study contributes a novel conceptual perspective for promoting responsible, ethical, and meaning-oriented uses of AI in educational contexts.